Effect of Egg White Addition on pH, Density, Emulsion Stability and Color of Mayonnaise - Fitri Suciati; Nurul Mukminah; Desy Triastuti (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
Mayonnaise can be made with the addition of egg whites, therefore it can increase the use of white egg. This work aimed to study the effect of egg whites addition on pH, density, emulsion stability and the color of mayonnaise. The research design using Completely Randomized Design (CRD) single factor, namely the level addition of egg white which consists of 4 treatments (0%, 5%, 10%, and 15%) with 3 replication. Parameters investigated were pH, density, emulsion stability and the color (brightness (L*), redness color (a*) and yellowness color (b*)) of mayonnaise. The data obtained was analyzed with ANOVA at Î± = 5%, and If there was a significant difference, the continue with the Dunnet test. The research result showed there were significant difference (P<0,05) in egg white level addition on the pH and brightness of the mayonnaise and did not significantly affect the density, emulsion stability, reddness, and yelloness color.